La gamificación con scratch como rincón de aprendizaje para el subnivel dos del currículo de educación inicial de los alumnos de educación inicial del centro de desarrollo infantil “Caritas Felices” durante el periodo lectivo 2015 - 2016. Lineamientos propositivos - Vega Trujillo, Pablo Arturo (2016)
The content of this paper refers, in the first instance to the "Gamification with Scratch as learning corner for the sublevel Two early education curriculum of the students of CDI Caritas Felices de Quito"; It is the overall objective: To investigate the incidence among the existing corner with scratch with early education curriculum found in the students of CDI Caritas Felices during the academic year 2015-2016. Therefore as the central problem, in this research I have determined How affects the gamification with Scratch as learning corner sublevel Two early education curriculum, students of Caritas Felices CDI during the academic year 2015 - 2016? The methods used for the preparation of this research work were: descriptive; He allowed detailing the current situation of the problem, ensuring its rational interpretation and analysis of the objective thereof, analytical; the critical study of the data obtained in the field research, statistical was made; It was used for the organization and development of graphics on the information obtained, scientist; It was used to check the results and draw conclusions and recommendations. The techniques and instruments were: Two surveys directed teachers to contrast before and after guideline purposeful, surveys used to determine compliance with specific goals; two tests of skills aimed at students to contrast a before and after the observation observation sheet, it served to contrast the incidence found among the corner, curriculum and student overall objective of this research. Although students of this level have not acquired the skill of reading and writing, or have established specific cognitive schemata, research shows that 83% of students feel confident and accept the learning corner with scratch 2.0, which means a significant fact shows that the educational community as a possible opening admire and replication of these educational corners. Similarly 83% of teachers acknowledge to use the corner to articulate the educational curriculum, a fact that means that the proactive guideline was drafted and implemented accurately, that the teaching staff has a desire to learn new concepts and tools, and that activity Traditional teaching can be improved with no costly investments.